Sarah's key - Rosnay, Tatiana de, 1961- (New York : St. Martin's Griffin, 2008)
On the sixtieth anniversary of the 1942 roundup of Jews by the French police in the Vel d'Hiv section of Paris, American journalist Julia Jarmond is asked to write an article on this dark episode during World War II and embarks on an investigation that leads her to long-hidden family secrets and to the ordeal of Sarah, a young girl caught up in the raid.
Includes readers' guide.
Keywords: Jews -- France -- Fiction; World War, 1939-1945 -- France -- Anniversaries, etc. -- Fiction; Americans -- France -- Fiction; Women authors -- Fiction; Family secrets -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; Paris (France) -- Fiction; Historical fiction